Environmental enterprising in the ecological system of relations: the problem of the legal institutionalization - Задихайло, Дмитро Дмитрович (Problems of legality, 2016)
The problem of the legal institutionalization of the relationship of the ecological system as a structural element of the Basic Law. It is noted that the level of constitutional and legal provision of environmental relations are at the level of declarative laconic. A circle of objects of the ecological system, and the valleys to get the constitutional provision on the basis of their social value and relevance. The attention to an environmental management mechanism in solving environmental problems and the need for extensive use of structures concept of sustainable development in the legal support of environmental system. Environmental management seems quite multidimensional phenomenon that can be realized both commercial and non-commercial basis and being specifically aimed at achieving environmental effect as goals, or being targeted to achieve profits, but in the production process to achieve optional environmental effect. As well as forming a separate constitutional institution – «ecological system».